PROSES PEMBUATAN BUSANA PESTA READY TO WEAR MONOCHROMATIC TRI-ANGLE - Edi Suwasana; Bryan Farrelinda Trimanta (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2020)
One type of clothing is ready to wear, in the form of ready-to-wear clothing. Currently this clothing is a trend, with monochrome colors and geometric motifs. The goal to be achieved is to make Monochromatic Tri-Angle ready-to-wear clothes. The data collection methodology used was in the form of observation, documentation, and literature. The fabric motif in the form of geometric shapes can be found on the Jepara Troso woven fabric. This outfit is based on a monochrome source of ideas, a triangle shape, and a Bird of Paradise. This dress is a party dress for non-formal parties. Consists of three parts, namely a long sleeved blouse with a balloon style with hidden buttons and no collar, a sleeveless outer length, then a custom skirt with a slit and a span skirt inside. Making ready to wear Monochromatic Tri-Angle party dresses includes several processes. The first is to make a design, then from the design it is developed into a pattern with a predetermined formula and size. After that cutting the material, laying the pattern on the fabric should be as much as possible so as not to waste a lot of material. Then the sewing process, which is combining the pieces of material. The last one is the solution, which includes attaching the rubbing stone application using a special tool, cleaning clothes from threads and ironing clothes to make them tidier.